Hamid, Eltigani Abdulqadir. “Civil Organization from a Qur’anic Perspective: A Study of the Foundations of the Islamic Social System," Year 4, Issue 15 (Winter 1419 AH/ 1999 CE), Pp. 7-49. - حامد, التيجاني عبد القادر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Eltigani Hamid’s article attempts to construct the Islamic social model from the Qur’an and raises a number of methodological issues facing the social scene. It explains key Islamic concepts such as chastity, modesty, immorality, kinship, the phenomenon of cutting ties of kinship and corruption in the land, and the Ummah. It addresses means of turning concepts into relational and institutional issues, and addresses the normative social provisions of the Qur’an, such as incest, social evils, marriage, divorce, custody, qualification, inheritance, punishment (retribution), and the waqf (endowment).